A novel approach using experimental results of mixed refrigerants and entropy-weighted TOPSIS optimization for the sustainability of hydrogen pre-cooling liquefaction process - Khan, Osama; Khan, Mohd Zaheen; Parvez, Mohd; Yahya, Zeinebou; Mahariq, Ibrahim; Alhodaib, Aiyeshah; Saleel, C. Ahamed; Agbulut, Umit (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
The global massive rise in consumption of power and energy has led to an increased elevation of the status of hydrogen energy as a primary clean fuel for the future. However, the liquefaction stage of hydrogen presents a real challenge because of the high power that accompanies the standard practices. This study investigates application of mixed refrigerants in the hydrogen liquefaction process. by creating and experimenting multiple combinations of mixed refrigerants. This work utilizes a novel approach in ranking mixed refrigerants on the criteria components. Notably, mixed refrigerant trial 5 emerges as the optimal choice, achieving a substantially improved Specific Energy Consumption (SEC) of 1.16 kWh/kgLH2 and Coefficient of Performance (COP) of 3.52. The optimized values result in a remarkable 72% reduction in SEC and a 57% enhancement in COP as compared to Joule-Brayton cycles, showcasing the potential for significant energy savings.
Keywords: Hydrogen liquefaction; Hydrogen pre-cooling; Mixed refrigerant; Optimization; Energy efficiency; PERFORMANCE; SYSTEM; Chemistry; Electrochemistry; Energy & Fuels